Near-complete phylogeny and taxonomic revision of the world’s babblers (Aves: Passeriformes) - Cai, Tianlong; Cibois, Alice; Alström, Per; Moyle, Robert G.; Kennedy, Jonathan D.; Shao, Shimiao; Zhang, Ruiying; Irestedt, Martin; Ericson, Per G.P.; Gelang, Magnus; Qu, Yanhua; Lei, Fumin; et al. (Molecular phylogenetics and evolution, 2019)
[Display omitted] •Dated phylogeny for babblers including 402 out of 452 currently recognized species.•Revealed the phylogenetic positions of some taxa previously not studied using newly generated sequences.•A new taxonomy for babblers with seven families and 64 genera, including one new family and one new genus. The babblers are a diverse group of passerine birds comprising 452 species. The group was long regarded as a “scrap basket” in taxonomic classification schemes. Although several studies have assessed the phylogenetic relationships for subsets of babblers during the past two decades, a comprehensive phylogeny of this group has been lacking. In this study, we used five mitochondrial and seven nuclear loci to generate a dated phylogeny for babblers. This phylogeny includes 402 species (ca. 89% of the overall clade) from 75 genera (97%) and all five currently recognized families, providing a robust basis for taxonomic revision. Our phylogeny supports seven major clades and reveals several non-monophyletic genera. Divergence time estimates indicate that the seven major clades diverged around the same time (18–20 million years ago, Ma) in the early Miocene. We use the phylogeny in a consistent way to propose a new taxonomy, with seven families and 64 genera of babblers, and a new linear sequence of names.